2007
DOI: 10.1002/qj.78
|View full text |Cite
|
Sign up to set email alerts
|

Iberian thermal lows in a changed climate

Abstract: ABSTRACT:Recent results from enhanced greenhouse-gas scenarios over southern Europe suggest that climate change implies a summertime mean surface warming of up to 4 K over the Iberian Peninsula. It is suggested that thermal lows, the most prominent Iberian summer weather, will undergo significant modifications in a changed climate. This is studied in the present paper by determining statistical features of the Iberian thermal low, at first for today's climate using data provided by ERA-40 and by the regional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Here we show that the combination of these two mechanisms results in the development of a heat low over the Mediterranean area that appears to be the dominant climate response in MSLP over that region. Our results are consistent with Hoinka et al [2007], who noted an intensification of the Iberian heat low in response to greenhouse warming.…”
Section: Discussionsupporting
confidence: 93%
“…Here we show that the combination of these two mechanisms results in the development of a heat low over the Mediterranean area that appears to be the dominant climate response in MSLP over that region. Our results are consistent with Hoinka et al [2007], who noted an intensification of the Iberian heat low in response to greenhouse warming.…”
Section: Discussionsupporting
confidence: 93%
“…However, the spatial resolution of that analysis is too coarse to elucidate finer scale wind flow patterns. Hoinka et al (2009) analyzed relationships between regional scale weather patterns and wildfires in central Portugal, namely the role of the Iberian thermal low (Hoinka and Castro, 2003;Hoinka et al, 2007). They showed that previously to days with extensive area burned, the atmospheric flow above Portugal is from the north, turning to easterly on the severe fire day, and to south-easterly afterwards.…”
Section: Discussionmentioning
confidence: 98%
“…Three data series were used in the current study: European Centre for Medium-Range Weather Forecasts (ECMWF) Reanalysis (ERA40) data; fire activity as provided by the Portuguese General Directorate of Forestry Resources (DGRF); and Iberian daily thermal low occurrence based on ERA40 taken from Hoinka et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the series of Iberian thermal low occurrence were taken from Hoinka et al (2007), containing the objectively determined occurrence of the Iberian thermal low based on ERA40 data. The related criteria can be found in Hoinka and Castro (2003).…”
Section: Methodsmentioning
confidence: 99%